2019
DOI: 10.1021/acs.inorgchem.9b02825
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Azido-Bridged Lanthanide Chain Complexes (Dy, Er, Gd, and Y) with a Pentadentate Schiff-Base [N3O2] Ligand: Synthesis, Structure, and Magnetism

Abstract: The syntheses, structure and magnetic properties are reported for five novel 1D polymeric azido-bridged lanthanide complexes with the general formula {[Ln-(DAPMBH)(N 3 )C 2 H 5 OH]C 2 H 5 OH} n where H 2 DAPMBH = 2,6-diacetylpyridine bis(4-methoxybenzoylhydrazone)a new pentadentate pyridine-base [N 3 O 2 ] ligand and Ln = Dy (1), Y 0.930 Dy 0.070 (2), Er (3), Y 0.923 Er 0.077 (4), and Gd (5). Xray diffraction analysis of 1−5 show that the central lanthanide atoms are eight-coordinated with the N 5 O 3 donor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 95 publications
1
18
0
Order By: Relevance
“…The room‐temperature χ M T value of 14.11 cm 3 mol −1 K is consistent with an isolated Dy 3+ center ( 6 H 15/2 , S =5/2, L =5, J =15/2, and g =4/3) with the expected χ M T value of 14.17 cm 3 mol −1 K. Upon decreasing the temperature, the χ M T value remains almost constant down to 70 K, below which it decreases to 10.52 cm 3 mol −1 K at 2 K, which is mainly attributed to the depopulation of m J sublevels and/or large magnetic anisotropy. The overall curve of the data is very similar to other mononuclear Dy 3+ SIMs and chain complexes [23,25,28] . In contrast, the χ M T curve of {Dy(DClQ) 3 (H 2 O) 2 } gradually descends upon cooling reaching a minimum of 12.6 cm 3 mol −1 K at 9.5 K and then increases upon further cooling to a maximum of 13.8 cm 3 mol −1 K at 2 K (Figure S6), which should be attributed to the presence of ferromagnetic coupling between the discrete Dy 3+ ions via strong hydrogen bonds and intermolecular π⋅⋅⋅π interaction.…”
Section: Figuresupporting
confidence: 64%
See 2 more Smart Citations
“…The room‐temperature χ M T value of 14.11 cm 3 mol −1 K is consistent with an isolated Dy 3+ center ( 6 H 15/2 , S =5/2, L =5, J =15/2, and g =4/3) with the expected χ M T value of 14.17 cm 3 mol −1 K. Upon decreasing the temperature, the χ M T value remains almost constant down to 70 K, below which it decreases to 10.52 cm 3 mol −1 K at 2 K, which is mainly attributed to the depopulation of m J sublevels and/or large magnetic anisotropy. The overall curve of the data is very similar to other mononuclear Dy 3+ SIMs and chain complexes [23,25,28] . In contrast, the χ M T curve of {Dy(DClQ) 3 (H 2 O) 2 } gradually descends upon cooling reaching a minimum of 12.6 cm 3 mol −1 K at 9.5 K and then increases upon further cooling to a maximum of 13.8 cm 3 mol −1 K at 2 K (Figure S6), which should be attributed to the presence of ferromagnetic coupling between the discrete Dy 3+ ions via strong hydrogen bonds and intermolecular π⋅⋅⋅π interaction.…”
Section: Figuresupporting
confidence: 64%
“…In the DyN 4 O 4 polyhedron of 1 , the Dy−O bond lengths are 2.344 and 2.374 Å, while the Dy−N bond distances are 2.542 and 2.374 Å. These bond distances are within the typically observed range for Dy complexes [21–24] . In addition, the average Dy−N bond distance (2.458 Å) in 1 is significantly short than the bond distance (2.524 Å) in {Dy(DClQ) 3 (H 2 O) 2 }.…”
Section: Figurementioning
confidence: 65%
See 1 more Smart Citation
“…Most of the complexes described in this work, in particular, the neutral complexes, 1-4, were obtained using the pentadentate ligand with the [N 3 O 2 ]-binding node, 2,6-diacetylpyridine bis-(4-methoxybenzoylhydrazone) [H 2 DAPMBH], that was synthesized by us via a ketonehydrazine condensation reaction between 1 equivalent of 2,6-diacetylpyridine and 2 equivalents of 4-methoxybenzoylhydrazine, in 96% ethanol [56]. We found that the interaction of anhydrous ErCl 3 with H 2 DAPMBH in absolute C 2 H 5 OH in the presence of 2 equivalents of the deprotonating agent, Et 3 N, leads to the formation and precipitation of pure neutral complex, [Er(DAPMBH)Cl(C 2 H 5 OH)] (1), practically insoluble in absolute ethanol with a very high yield.…”
Section: Synthesis and Molecular Structurementioning
confidence: 99%
“…Ligands [H 2 DAPMBH] and [H 4 DAPS] were synthesized according to the published procedures [40,43,56].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%